KNOWLEDGE AND ATTITUDE OF HYPERTENSIVE PATIENTS TOWARDS DIETARY MANAGEMENT AT ENTEBBE REGIONAL REFERRAL HOSPITAL IN WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Nantaba, Damalie; Namubiru, Rebecca; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student's Journal of Health Research Africa, 2025)
Background. Hypertension is one of the most crucial health problems and chronic diseases in developed and underdeveloped countries, which is further expanded due to ignorance and lack of knowledge. The study assessed the knowledge and attitude of hypertensive patients towards dietary management at Entebbe Regional Referral Hospital in the Wakiso district. Methodology. A cross-sectional study design was used, employing a quantitative approach to collect data using a semi-structured questionnaire from 36 participants. The information was manually tallied; thereafter, Microsoft Word and Excel programs were employed, followed by presentation in the form of frequency tables, graphs, and figures like pie charts and bar graphs. Results. Most respondents were in the age range of above 50 years (47.2%), (44.4%) had attained secondary education, (61.1%) had good knowledge, 20 (55.6%) of the respondents were not familiar with salt content in common foods, 32 (88.9%) knew the foodstuffs restricted in hypertension, (47.2%) knew that reducing salt intake can help manage hypertension, (94.4%) agreed that consuming a diet rich in fruits vegetables whole grains and proteins positively impact blood pressure. 30(83.3%) participants had a positive attitude towards adding fruits and vegetables to their diet, and 21 (58.3%) respondents strongly agreed that physical exercises have an impact on blood pressure. Conclusion. The majority of the participants had good knowledge regarding the relevant dietary approaches needed to stop hypertension. A significant number of the respondents had a positive attitude toward the dietary modifications for proper hypertension control. Recommendations. The Ministry of Health and other responsible bodies should strive to increase the awareness and knowledge of hypertensive patients about the importance of consultation and seeking medical services.